Semiotic analysis of song lyrics entitled “Nanti Kita Seperti Ini” - Anjelika, Sela (Jurnal Penelitian Humaniora, 2025)
This article examines the meaning of happinness in the lyrics of the song “Nanti Kita Seperti Ini” by Batas Senja through Roland Barthes’ semiotic analysis. Roland Barthes’ semiotic theory is used to explain the denotation, connotation, and myth of the meaning of happiness contained in the song lyrics. The research method used is a qualitative descriptive approach with an interpretative model. The data collection technique used in this research is a document study technique through tracing various sources relevant to the topic being analyzed. The results of Roland Barthes; semiotic study on the lyrics of the song “Nanti Kita Seperti Ini” by Batas Senja are as follows. The denotation meaning shows the feeling of great love and the desire to interpret happiness together. The connotation meaning relates to the human connection in nterpreting happiness armed with faith in God. Meanwhile, the myth contained in the song lyrics is cooperation in relationships to define happiness itself.